Knowledge, attitude and practice of emergency medical care in Lima, Peru - Adler, David Aaron; Goldstein, Max Dean; Mai, Anthony Phy; Tello, Miguel Rosales; Donaldson, Ross Ireland; Donaldson, Ross Ireland (International Journal Of Community Medicine And Public Health, 2019)
Background: This study gauged public need and reception for a community-based first-aid and cardiopulmonary resuscitation (CPR) training program in Lima, Peru, to counteract predicted emergency medical service (EMS) deficits. Methods: The study population consisted of Lima households that were selected with a two-staged 30x7 cluster sampling method. An EMS and first-aid focused knowledge-attitude-practice (KAP) survey was administered by a joint academic-community interview team. Results: The study included 210 households from 30 districts within Lima. Among the participants, 61.4% were unable to provide an EMS number and only 24.8% would call an ambulance in case of a family emergency. Although 37.6% could provide first-aid, 99.5% would feel more comfortable if a neighbor were first-aid trained. Conclusions: The results indicated a lack of confidence in Lima’s EMS systems and awareness of EMS contact numbers, which possibly led community members to trust each other over their local EMS. The creation of a community-based first-aid and CPR training program can potentially take advantage of strong intra-community trust, mitigate first-aid deficits, and alleviate Lima’s injury burden by providing a buffer against barriers to effective EMS responses.